Forest regeneration can positively contribute to local hydrological ecosystem services: Implications for forest landscape restoration. Issue 4 (22nd February 2021) - van Meerveld, H. J. (Ilja); Jones, Julia P. G.; Ghimire, Chandra P.; Zwartendijk, Bob W.; Lahitiana, Jaona; Ravelona, Maafaka; Mulligan, Mark
Abstract: Governments are increasingly committing to significant forest restoration. While carbon sequestration is a major objective, the case for restoration often includes benefits to local communities. However, the impacts of forest restoration on local hydrological services (e.g. flood and erosion risk, stream flow during dry periods) are surprisingly poorly understood. Particularly limited information is available on the impacts of passive tropical forest restoration following shifting cultivation. The outcome depends on the trade‐off between the improved soil infiltration capacity (reducing overland flow and increasing soil and groundwater recharge) and greater evapotranspiration (diminishing local water availability). Using measurements from highly instrumented plots under three vegetation types in the shifting cultivation cycle in Madagascar's eastern rainforests (forest, tree fallow and degraded abandoned agricultural land), and infiltration measurements for the same vegetation types across the landscape, we explore the impacts of forest regeneration on the ecohydrological processes that underpin locally important ecosystem services. Overland flow was minimal for the tree fallow (similar to the forest) and much lower than for the degraded land, likely leading to a lower risk of erosion and flooding compared to the degraded land. Conversely, evapotranspiration losses were lower for the tree fallow than the forest, leading to a higher net recharge, likely resulting in more streamflow between rainfall events. These results demonstrate that young regenerating tropical forest vegetation can positively contribute to locally important hydrological ecosystem services. Allowing tree fallows to recover further is unlikely to further reduce the risk of overland flow but may, at least temporarily, result in less streamflow. Synthesis and applications . Encouraging natural regeneration is increasingly seen as a cost‐effective way to deliver forest landscape restoration. Our data suggest that increasing the abundance of young secondary forest in the tropics, by increasing fallow lengths in the shifting cultivation cycle, could make a positive contribution to locally important hydrological ecosystem services (specifically reducing overland flow and therefore erosion and flooding, while maintaining streamflows). Such empirical understanding is needed to inform the models used for planning forest landscape restoration to maximize benefits to local communities. Abstract : Encouraging natural regeneration is increasingly seen as a cost‐effective way to deliver forest landscape restoration. Our data suggest that increasing the abundance of young secondary forest in the tropics, by increasing fallow lengths in the shifting cultivation cycle, could make a positive contribution to locally important hydrological ecosystem services (specifically reducing overland flow and therefore erosion and flooding, while maintaining streamflows). Such empirical understanding is needed to inform the models used for planning forest landscape restoration to maximize benefits to local communities. Résumé: Les gouvernements s'engagent de plus en plus et de manière significative dans la restauration des forêts. Si la séquestration du carbone en est l'objectif majeur, les arguments en faveur de la restauration englobent des bénéfices des communautés locales. Cependant, les services rendus par l' hydrologie à travers la restauration des forêts concernant, par exemple, les risques d'inondation et d'érosion et le soutien des débits des cours d'eau pendant les périodes sèches, sont encore peu compris. En particulier, les informations disponibles sur les impacts de la restauration passive des forêts tropicales suite à l'agriculture itinérante restent encore limitées. Le résultat dépend du bilan final entre deux effets antagonistes : l'amélioration de la capacité d'infiltration des sols limitant le ruissellement de surface et augmentant la recharge des nappes d'une part, et la hausse des pertes par évapotranspiration diminuant ainsi la disponibilité locale en eau, d'autre part. Les impacts de la régénération des forêts tropicales de l'est de Madagascar (forêt, jachère arborée, et terres agricoles dégradées et abandonnées) sur les processus hydrologiques sont examinés en utilisant des mesures réalisées sur des parcelles instrumentées couvertes par les trois types de végétation rencontrés au cours du cycle de l'agriculture itinérante et des mesures d'infiltration sur des sites de mêmes types de végétation dans le secteur d'étude. Les jachères et la forêt présentent de taux de ruissellement de surface similaires et beaucoup plus faibles que ceux dans les terres dégradées, avec pour conséquence des risques d'érosion et d'inondation plus faibles pour ces deux types de végétation que pour les terres dégradées. À l'inverse, les pertes par évapotranspiration pour les jachères sont plus faibles comparées à celles dans les forêts, induisant une recharge nette plus importante et entraînant probablement des débits dans les cours d'eau plus soutenus entre les épisodes de pluie. Ces résultats montrent que la jeune végétation de forêts tropicales en régénération peut contribuer de manière positive à l'hydrologie locale. Permettre aux jachères arboricoles de se régénérer davantage ne garantira pas une poursuite de la réduction des risques de ruissellement de surface, mais de telles pratiques peuvent diminuer le débit des cours d'eau, au moins temporairement. Synthèse et applications . Encourager la régénération naturelle est de plus en plus considéré comme un moyen rentable de restaurer les paysages forestiers. Nos données suggèrent que l'augmentation de l'abondance de jeunes forêts secondaires dans les tropiques, en allongeant la durée des jachères dans le cycle de l'agriculture itinérante, contribue positivement aux services écosystémiques de l'hydrologie à l'échelle (en particulier, à la réduction du ruissellement en surface et, donc, de l'érosion et des inondations, tout en maintenant les débits des cours d'eau). Ces études empiriques sont nécessaires pour renseigner les modèles utilisés pour planifier la restauration des paysages forestiers afin de maximiser les bénéfices de la régénération pour les communautés locales.